Implementation of Batik Colouring Using Jengkol Peels Extract at Rang Minang Batik House in Padang Panjang City - Wulandari, Indah; Efi, Agusti (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
The use of synthetic dyes in the batik industry, considered practical and efficient, has had negative impacts on health and the environment. This study aims to explore the production and application of natural dye extracts from jengkol (Archidendron pauciflorum) peels as an alternative dye in the batik dyeing process at Rumah Batik Rang Minang. A descriptive qualitative approach was used, with data collection methods including documentation, interviews, and observation. The study results show that the jengkol peel extract is produced through a boiling process and applied to batik fabric using the dipping technique. The dyeing process involves soaking the fabric in jengkol peel extract and repeating the dipping to ensure color durability. The use of this extract produces a distinctive and long-lasting color, offering an eco-friendly solution for the batik industry.